Absurd jako mechanizm sensotwórczy: kreowanie aberracyjnego wizerunku medialnego w ramach strategii dyskredytacji - Jaskólski, Adam (Przegląd Rusycystyczny, 2018)
АНТИПРАВИТЕЛЬСТВЕННЫЕ АКЦИИ В РОССИИ ГЛАЗАМИ РОССИЙСКИХ ВЛАСТЕЙ И КРЕМЛЁВСКИХ СМИ Р е з ю м е Целью настоящего исследования является представить основные положения нарратива российских властей и подчинённых им СМИ об антикоррупционных протестных акциях, проходивших в российских городах 26 марта и 12 июня 2017 г. Выделяются и анализируются языковые средства, употреблявшиеся для формирования образа упомянутых антикоррупционных протестов. Проанализированный материал представляет собой пример проводимой в последние годы в провластных российских СМИ сильной дискредитации противников и критиков нынешнего режима. Последняя, в свою очередь, является одним из основных компонентов идеологической кампании Кремля, главной целью которой, по нашему мнению, является сплочение российского населения и, следовательно, предотвращение „цветной революции” в России. THE NARRATIVE OF THE RUSSIAN AUTHORITIES AND PRO-GOVERNMENT MEDIA ABOUT ANTI-GOVERNMENT ACTIONS IN RUSSIA S u m m a r y The main aim of this paper is to present the basic assumptions of the Kremlinʼs narrative about anti-government actions that took place in Russia on 26th of March and 12th of June 2017. The author extracts and analyzes linguistic expressions which were regularly used in the statements of the Russian authorities and texts that were published in the Russian media in order to build the image of the internal opposition and its supporters as well as the demonstrations carried out by them. The analyzed material fits in the intensely conducted since 2012 discrediting of the opponents and critics of the current Russian authorities which in turn is one of the basic elements of the ideological offensive of the Kremlin whose main goal, according to the author, is to unite or maintain the unity of Russian society, thereby to prevent the “colour revolution” in Russia.